Actualizing the rights of people living with disabilities (PWDS) in development policies, planning and programming in Africa : a review of selected country experiences - Tigere, B.; Moyo, T. (International Conference on Public Administration and Development Alternatives (IPADA), 2019)
Exclusion and marginalisation of people living with disabilities is an on-going challenge in Africa in spite of the existence of international conventions such as the United Nations Convention on the Rights of Persons with Disabilities (UN CRPD) which obliges member states to promote the equal rights to development of that segment of the population. Africa's Agenda 2063 and UN Agenda 2030 on Sustainable Development Goals also support the principle. The paper therefore aims to assess the performance of African countries in integrating the developmental priorities of people with disabilities into their development policies, planning and programming. Its main objectives are to identify the current state of practice, identify best practices and draw lessons. The methodological approach is a qualitative desk study. The Social Model of disability is adopted as the theoretical framework of analysis. It is selected because it shifts from dominant traditional welfarist approaches in favour of transformation, empowerment and participative action of people with disabilities. Key findings point to mixed success among the five country cases in terms of domestication on international and continental instruments on the rights of people with disabilities. However, generally they are performing poorly in terms of full implementation of those policies and laws. The paper recommends that the countries should strengthen both implementation machineries as well as capacities at all levels.
Journal article published in The 4th Annual International Conference on Public Administration and Development Alternatives 03 - 05 July 2019, Southern Sun Hotel, OR Tambo International Airport, Johannesburg, South Africa
Keywords: Disability; Empowerment; Participation transformative development; People with disabilities; People with disabilities -- Government policy; Discrimination against people with disabilities -- Africa